عزل الفطر Beauveria bassiana (Bals.)Vuil. وتقييم فاعليته على يرقات و عذارى دودة ورق القطن Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae) (Latakia University Journal -Biological Sciences Series, 2017)
تم عزل 6 عزلات من الفطر Beauveria bassiana من الترب المحلية في الساحل السوري من أنظمة بيئية طبيعية وزراعية مختلفة، باستخدام يرقات العمر الأخير من دودة الشمع الكبرى كطعم (Galleria bait method). بلغت القدرة الإمراضية للعزلات الست على يرقات دودة الشمع الكبرى Galleria mellonella بالعمر الأخير 100% كنسبة مئوية للموت بعد 3-5 أيام من المعاملة. اختبرت فاعلية العزلات على يرقات العمر الثالث لدودة ورق القطن Spodoptera littoralis لاختيار العزلة الأكثر شراسة على هذه الآفة. تراوحت النسب المئوية للموت بين 75-100% لجميع العزلات في اليوم الخامس من المعاملة، استخدم المعلق البوغي للفطر B. bassiana بالتركيز 106 بوغ/مل للعزلة التي تم اختيارها رشاً على عذارى دودة ورق القطن وبلغت النسبة المئوية لخروج البالغات 42% مقارنة مع الشاهد.Six different isolates of the fungus Beauveria bassiana were isolated from local soils, which collected from two different ecosystems (Natural and Cultivated), at the Syrian Coastal region, using the "Galleria Bait Method". The mortality caused by these fungal isolates against Galleria mellonella larvae was 100% after 3- 5 days post treatment. The pathogenicity of these isolates was studied against 3rd instar larvae of Spodoptera littoralis to detect the most virulent isolate. The mortality ranged from 75% to 100% for the all isolates at the 5th day post treatment. Spore suspension of the most virulent isolate was used at concentration 106spore/ml by spraying it on the pupae of S. littoralis. The percentage of adult emergence was 42% in the fungal treatment compared to the control treatment.